2012
DOI: 10.1086/665710
|View full text |Cite
|
Sign up to set email alerts
|

Use of Administrative Data in Efficient Auditing of Hospital-Acquired Surgical Site Infections, New York State 2009–2010

Abstract: Audits are vital for ensuring the accuracy of hospital-acquired infection (HAI) data so that hospital HAI rates can be fairly compared. Use of administrative data increased the efficiency of identifying problems in hospitals' SSI surveillance that caused SSIs to be unreported and caused errors in denominator data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…This database has been consistently criticized for its inaccuracies. 13, 14 In this study, we also found that within our Partners Colorectal Collaborative the data gathered for this database can reach diametrically opposed conclusions when compared to data collected to measure surgical quality in the NSQIP database. These differences in reported infection rates and their subsequent conclusions appeared to be non-random.…”
Section: Discussionmentioning
confidence: 60%
“…This database has been consistently criticized for its inaccuracies. 13, 14 In this study, we also found that within our Partners Colorectal Collaborative the data gathered for this database can reach diametrically opposed conclusions when compared to data collected to measure surgical quality in the NSQIP database. These differences in reported infection rates and their subsequent conclusions appeared to be non-random.…”
Section: Discussionmentioning
confidence: 60%
“…The scope of reported secondary uses included for conducting epidemiological and pharmacovigilance research studies, for facilitating recruitment to randomised controlled trials14 – 16 and for carrying out audits and benchmarking studies 17 , 18. We also found secondary uses being used for financial and service planning, incident tracking, the teaching of clinical staff and billing 19 , 20…”
Section: Resultsmentioning
confidence: 93%
“…In Scotland 77 researchers found that 91% of eligible procedures were included in the surveillance data. In the US (New York) 78 researchers found 98% matches between administrative data and surveillance data. A study from England found that the surveillance database contained 95% of the procedures that were recorded in the patient administration system.…”
Section: Completeness and Accuracy Of The Procedures Denominatormentioning
confidence: 99%
“…Although traditional case-finding by ICPs has been considered the "gold standard" of HAI surveillance, several newer studies show that this is not necessarily the case: computer-aided surveillance may be more time-efficient and superior in case-finding. Many studies have compared traditional surveillance by ICPs with case-finding using surveillance definitions to available data sources such as ICD-9 diagnostic codes and other administrative coding; 78,81,87,89,[177][178][179][180][181] microbiology, laboratory or pharmacy data; [182][183][184][185] or a combination of these 84,137,146,184,[186][187][188][189] . Some have utilized advanced algorithms to detect SSIs and validate these against ICP case-finding.…”
Section: Positive Aspects Of Automated Case-findingmentioning
confidence: 99%